4-H Student Nutrition Advisory Councils Support Positive Youth Development and Health Outcomes Among Underserved Populations - Shannon Klisch; Katherine E. Soule ([TEST] Journal of Extension, 2021)
4-H SNAC Clubs engage youth in low-income schools with majority Latinx enrollment in leadership activities to increase schoolwide health and wellness. 4-H SNAC Clubs aim to develop youth health leaders, establish youth-adult partnerships, and increase access to 4-H in Latinx communities. Outcomes related to healthful living and positive youth development were assessed using the Teen Teacher Retrospective Survey (n=59) across five 4-H SNAC Clubs. Results show positive outcomes related to self-reported health behaviors for students and their families and leadership development. 4-H SNAC Clubs can increase access to 4-H among Latinx youth and support healthier communities through the Supplemental Nutrition Assistance Program – Education programming.
Keywords: Positive youth development; nutrition education; low-income communities; Latinx youth; health equity